The South African Volatility Index (SAVI) as a tool for market timing on the Johannesburg Stock Exchange (JSE) - Govender, Lerissa (Department of Finance and Tax, 2019)
This study tests the viability of using the South African Volatility Index (SAVI) as a tool to time equity trades on the Johannesburg Stock Exchange (JSE), and uses technical analysis in the application of selected market timing trading strategies. This study therefore has very real practical relevance to investors on the JSE, who wish to take an active approach to investing. Using the JSE Top 40 Index for the period May 2007 to March 2018 as a sample, this investigation firstly considers whether the technical trading rules developed for the CBOE VIX, as used in the United States market, can be applied to the South African market using the SAVI as a market timing tool in order to outperform a passive buy-and-hold strategy. This involved switching the portfolio between the Top 40 equity index and the STeFI money market index, depending on the nature of the timing signals generated by the SAVI-based strategies. Secondly, this study considers the viability of using the SAVI in a market timing rule to take advantage of the documented size (small-capitalisation versus large-capitalisation) and style (value versus growth) anomalies on the JSE. In the first part of this study, it was found that three of the eleven market timing trading strategies outperformed the buy-andhold strategy before the inclusion of transaction costs. When compared to the results found by the researchers in the U.S context, it appears that these strategies are more successful in the U.S context using the VIX, as the majority of the trading strategies yielded positive excess returns over their respective sample periods. Additionally, in the second part of this study, it was found that the returns of the style strategy were not significant enough to deem it a profitable market timing strategy. However, the returns of the size strategy were significant enough to make it a profitable strategy. Transaction costs, applied at different levels, had a significant impact on the results of all strategies, with only one of the market timing strategies, namely the simple moving average strategy, beating the buy-and-hold strategy after transaction costs of up to 0.2% and 0.45% (for sales and purchases respectively) have been taken into account.